PERANCANGAN SISTEM INFORMASI PENJUALAN BERAS BERBASIS WEB METODE PROTOTIPE PADA HELER FAJAR - Niki Wilni Diana Niki; Hani Salsabila; M. Fikri Bafadhal; Oka Ediansa (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2026)
The advancement of information technology encourages business actors to optimize their operational processes through the implementation of computerized systems. Gilingan Padi Fajar in Olak Kemang Village still conducts its operational activities manually, including stock recording, sales transactions, and report preparation, which leads to various issues such as delays in data processing, potential recording errors, and limited access to information for customers. This study aims to design a web-based rice sales information system capable of integrating data management, transaction processing, and reporting into a single integrated platform. The method used in this study is the prototype method, which enables iterative system development through direct interaction with users to ensure alignment with actual needs in the field. The results show that the designed system can improve the efficiency of data processing, simplify the ordering process without requiring customers to visit the location directly, and generate sales reports more quickly and accurately. Therefore, this system is expected to support improved operational performance and service quality at Gilingan Padi Fajar.